Integrative governance: challenges for the senior public service - Thynne, Ian (1998)
The aim of this introductory article is to consider but three aspects of the changing nature of government which are of particular importance and which serve generally as a backdrop to the discussions in subsequent articles. All three pose integrative-type challenges especially for senior officials and each has consequences for education and training in keeping with IASIA's major interest in the development of human resources. The first concerns the extent and implications of work differentiation through a process of atomization. The second relates to the management of public affairs as a multisectoral endeavour. The third underlies the other two in that it involves fundamental questions of professionalism, morality and accountability
Keywords: Civil service